Effect of pressure on paraconductivity in HoBa₂Cu₃O₇-δ single crystals with oxygen deficiency - Tiutierieva, K.V.; Dovgopolova, Ya.V.; Chernovol-Tkachenko, O.O.; Ivrij, I.L.; Vovk, R.V.; Prihod'ko, S.I. (Functional Materials, 2016)
In this work, we have investigated the effect of high pressure on conductivity in basal plane of the high temperature super conducting single crystals HoBa₂Cu₃O₇-δ with oxygen deficiency. It has been determined that the excess conductivity Δσ(T) of HoBa₂Cu₃O₇-δ single crystals in temperature interval near the critical temperature (Tc) is described within the framework of the Aslamazov-Larkin theoretical model. It has been shown that evolution of the transverse coherence length ξc(0) in the case of application/removal of the high pressure is largely determined by the "relaxation" pressure effect during prolonged exposure of the sample under load at the room temperature.